Performance Evaluation of LoRa in Farm Irrigation System with Internet of Things - Kurniawan Dwi Irianto (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2022)
Long Range (LoRa) Communication is one of the emerging Internet of Things (IoT) technologies and has been widely discussed by researchers. LoRa is also part of the Low Power Wide Area Networks (LPWAN) technology where this technology focuses on communication systems on energy efficiency, wide coverage, low data rates, and long battery life. LoRa uses industrial, scientific, and medical (ISM) radio frequencies. These frequencies can be used for free without paying for a license. Theoretically and under ideal conditions, the LoRa range can reach < 3 km in urban areas and > 3 km in rural areas. However, only a few studies discuss the evaluation and analysis of LoRa performance, which is implemented in the real world with particular case studies. This article aims to evaluate and analyze the performance of LoRa, which is applied to a case study of an IoT-based agricultural irrigation system. Several parameters will be assessed and analyzed, including distance, received signal strength indication (RSSI), spreading factor, coding rate, power transmission, and packet delivery ratio (PDR). Experimental and measurement results show that LoRa can transmit data packets up to a distance of 2.5 km but with a very low PDR rate of around 5-7%. The results also show that LoRa can work optimally if the distance is > 1 km with a PDR rate of about 70-100%.